SETTLEMENT OF INTERNATIONAL DISPUTES IN THE BODY OF ASEAN: Treaty of Amity and Cooperation in Southeast Asia - Tiara Almira Raila; Clara Puspa Jelita (Universitas Pakuan, 2020)
ABSTRACT Founded in 1967, the Association of South East Asian Nation or ASEAN was formed as an attempt to create cooperation and solidarity between fellow ASEAN members. Through the years of its existence, relations between ASEAN members in various aspects have developed and have been carried out through agreements and cooperation. However, in implementing agreements and through the cooperation of one or more members within the ASEAN region, countries with different backgrounds and interests are very likely to disagree at some point which would then create a dispute between them. Although formed in order to create peace within its region, disputes within ASEAN region are seldom settled as ASEAN members strongly hold the principles of sovereignty of each member states and the use of non-intervention. Through this background, the Authors of this paper will then study the settlement of international disputes in the body of ASEAN and as to why the principles and objectives of ASEAN and the concept of regional organizations have not been able to work well in ASEAN.Keywords: International Dispute Settlement, ASEAN, Treaty of Amity and Cooperation in Southeast Asia ABSTRAK Ditemukan pada tahun 1967, Association of South East Asian Nation atau ASEAN dibentuk sebagai upaya untuk menciptakan kerjasama dan sebagai bentuk solidaritas dari setiap negara anggota ASEAN. Selama perjalanannya, hubungan antara negara anggota ASEAN di berbagai aspek telah berkembang dan dilaksanakan melalui berbagai macam bentuk perjanjian dan kerjasama. Namun dalam pelaksanannya, sangat dimungkinkan untuk terciptanya suatu sengketa diantara negara-negara anggota yang memiliki latar belakang serta kepentingan yang berbeda- beda. Meskipun ASEAN dibentuk dalam rangka menciptakan perdamaian di dalam wilayahnya, sengketa dalam lingkup ASEAN sering tidak dapat terselesaikan. Hal tersebut dikarenakan negara anggota ASEAN yang berpegang teguh pada prinsip kedaulatan setiap negara dan non-intervensi. Berdasarkan latar belakang tersebut, Penulis penelitian ini akan meneliti mengenai penyelesaian sengketa internasional di dalam tubuh ASEAN dan mengapa prinsip dan tujuan dari ASEAN serta konsep organisasi regional belum dapat bekerja sebagaimana mestinya di wilayah ASEAN. Keywords: Penyelesaian Sengketa Internasional, ASEAN, Perjanjian Persahabatan dan Kerja Sama di Asia Tenggara